AKTIVITAS ANTIBAKTERI SALEP EKSTRAK DAUN SUKUN (Artocarpus altilis) DENGAN DUA MACAM KOMBINASI BASIS SALEP TERHADAP BAKTERI Stapylococcus aureus - Dewi Andini Kunti Mulangsri; Heru Fitranto; Yana Astiana; Mufrod Mufrod (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACT Breadfruit leaves (Artocarpus altilis) was contain compound of flavonoids, tannins and phenol that the ability as antibacterial against Staphylococcus aureus bacteria. The extracts of breadfruit leaves formulated became ointment that made practice to used. The combine of ointment bases can obtain of good consistency like the combine of adeps lanae with vaselin album and cera flava with vaselin album. The aims of this study to know the profile of antibacterial activity of the breadfruit leaves extract ointment with two kind of the combine of ointment bases. The breadfruit leaves extract has obtained by maceration method used etanol 70% solvents. The breadfruit leaves ointment was made by melting method with combination bases A is adeps lanae:vaselin album as F1 (13.5%:76.5%), F2 (45%:45%) dan F3 (76.5%:13.5%), while combination B is cera alba:vaselin album as F1 (85.5%:4.5%), F2 (81%:9%), F3 (76.5%:13.5%). antibacterial activity assay was used well diffusion method and analyzed descriptively. The research result that the all formulas has breadfruit flavor, smooth texture and brown color. Two variatons of combination bases ointment has antibacterial activity against Staphylcoccus aureus bacteri with formed of inhibition zone around the well. Keywords: Breadfruit leaves extract, ointment, antibacterial, combination of ointment bases